(untitled) (Communications in Computational Chemistry, 2017)
A new molecule 9,10-dihydroxybenzo[h] quinoline (i.e. 9-10-HBQ) is focused in the present work about its excited state proton transfer (ESPT) mechanism. Though comparing potential energy barriers, it is found that the ultrafast ESPT process could occur in the S_1 state without potential energy barrier along with hydrogen bond O_3-H_4···N_5 forming 9-10-HBQ-PT1 structure, subsequently, the second proton transfers via another intramolecular hydrogen bonded wire O_1-H_2···N_3 with a low potential energy barrier (about 7.69 kcal/mol) in the S_1 state forming 9-10-HBQ-PT2 configuration. After completing excited state dynamical process, the S_1-state could turn back to S_0 state with occurring reversed ground state proton transfer forming initial 9-10-HBQ structure.